Preoperative Chemotherapy for Operable Colon Cancer: Mature Results of an International Randomized Controlled Trial. Issue 8 (10th March 2023) - Morton, Dion; Seymour, Matthew; Magill, Laura; Handley, Kelly; Glasbey, James; Glimelius, Bengt; Palmer, Andy; Seligmann, Jenny; Laurberg, Søren; Murakami, Keigo; West, Nick; Quirke, Philip; et al.
Abstract : PURPOSE: Neoadjuvant chemotherapy (NAC) has potential advantages over standard postoperative chemotherapy for locally advanced colon cancer but requires formal evaluation. METHODS: Patients with radiologically staged T3-4, N0-2, M0 colon cancer were randomly allocated (2:1) to 6 weeks oxaliplatin-fluoropyrimidine preoperatively plus 18 postoperatively (NAC group) or 24 weeks postoperatively (control group). Patients with RAS -wildtype tumors could also be randomly assigned 1:1 to receive panitumumab or not during NAC. The primary end point was residual disease or recurrence within 2 years. Secondary outcomes included surgical morbidity, histopathologic stage, regression grade, completeness of resection, and cause-specific mortality. Log-rank analyses were by intention-to-treat. RESULTS: Of 699 patients allocated to NAC, 674 (96%) started and 606 (87%) completed NAC. In total, 686 of 699 (98.1%) NAC patients and 351 of 354 (99.2%) control patients underwent surgery. Thirty patients (4.3%) allocated to NAC developed obstructive symptoms requiring expedited surgery, but there were fewer serious postoperative complications with NAC than with control. NAC produced marked T and N downstaging and histologic tumor regression (all P < .001). Resection was more often histopathologically complete: 94% (648/686) versus 89% (311/351), P < .001. Fewer NAC than control patients had residual or recurrent disease within 2 years (16.9% [118/699] v 21.5% [76/354]; rate ratio, 0.72 [95% CI, 0.54 to 0.98]; P = .037). Tumor regression correlated strongly with freedom from recurrence. Panitumumab did not enhance the benefit from NAC. Little benefit from NAC was seen in mismatch repair–deficient tumors. CONCLUSION: Six weeks of preoperative oxaliplatin-fluoropyrimidine chemotherapy for operable colon cancer can be delivered safely, without increasing perioperative morbidity. This chemotherapy regimen, when given preoperatively, produces marked histopathologic down-staging, fewer incomplete resections, and better 2-year disease control. Histologic regression after NAC is a strong predictor of lower postoperative recurrence risk so has potential use as a guide for postoperative therapy. Six weeks of NAC should be considered as a treatment option for locally advanced colon cancer.